"We want freedom and citizenship" : documents of Salish, Pend d'Oreille, and Kootenai Indian history, 1912-1920 - Bigart, Robert; McDonald, Joseph, 1933- (Salish Kootenai College Press, 2021)
"The years between 1912 and 1920 were a period of economic and political struggle for the Salish, Pend d'Oreille, and Kootenai tribes of the Flathead Indian Reservation in western Montana. The Indian people toiled to maintain their economic independence despite the theft of their land assets. The new Flathead Irrigation Project destroyed most of the private irrigation ditches tribal farmers had dug over the years. Some tribal members opened businesses and organized rodeos, but many ventures were frustrated by government policies, fire, and drought. While trying to adapt to the economic impact of allotment, the tribes also fought against paternalistic and exploitative government policies"--